Five Trends in Physical Education Teacher Education. Issue 6 (23rd July 2020) - Ward, Phillip; Cho, Kyuil
Abstract: In this article we present five trends that are impacting physical education teacher education (PETE). The trends are (a) practice-based teacher education that refines the knowledge base for teacher education, (b) core teaching practices that define the critical teaching practices for successful lifelong teaching, (c) pedagogies of practice that operationalize practice-based teacher education with core practices, (d) the reconnection of health education with physical education, and (e) the Whole School, Whole Community, Whole Child model. We describe each trend, discuss related policy implications and provide examples of how to use these trends in PETE.